Characterization, biological activity, and anticancer effect of green-synthesized gold nanoparticles using Nasturtium officinale L. - Ozlem Tonguc Yayintas; Neslihan Demir; Fadime Canbolat; Tülay Kiliçaslan Ayna; Melek Pehlivan (BMC, 2024)
Abstract Background Nanostructured materials used have unique properties and many uses in nanotechnology. The most striking of these is using herbal compounds for the green synthesis of nanoparticles. Among the nanoparticle types used for green synthesis, gold nanoparticles (AuNPs) are used for cancer therapy due to their stable structure and non-cytotoxic. Lung cancer is the most common and most dangerous cancer worldwide in terms of survival and prognosis. In this study, Nasturtium officinale (L.) extract (NO), which contains biomolecules with antioxidant and anticancer effects, was used to biosynthesize AuNPs, and after their characterization, the effect of the green-synthesized AuNPs against lung cancer was evaluated in vitro. Methods Ultraviolet‒visible (UV‒Vis) spectrophotometry, scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), multiple analysis platform (MAP), and Fourier transform infrared (FT-IR) spectroscopy analyses were performed to characterize the AuNPs prepared from the N. officinale plant extract. Moreover, the antioxidant activity, total phenolic and flavonoid contents and DNA interactions were examined. Additionally, A549 lung cancer cells were treated with 2-48 µg/mL Nasturtium officinale gold nanoparticles (NOAuNPs) for 24 and 48 h to determine the effects on cell viability. The toxicity of the synthesized NOAuNPs to lung cancer cells was determined by the 3-(4,5-dimethylthiazol-2-il)-2,5-diphenyltetrazolium bromide (MTT) assay, and the anticancer effect of the NOAuNPs was evaluated by apoptosis and cell cycle analyses using flow cytometry. Results The average size of the NPs was 56.4 nm. The intensities of the Au peaks from EDS analysis indicated that the AuNPs were synthesized successfully. Moreover, the in vitro antioxidant activities of the NO and NOAuNPs were evaluated; these materials gave values of 31.78 ± 1.71% and 31.62 ± 0.46%, respectively, in the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay at 200 g/mL and values of 25.89 ± 1.90% and 33.81 ± 0.62%, respectively, in the 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay. The NO and NOAuNPs gave values of 0.389 ± 0.027 and 0.308 ± 0.005, respectively, in the ferrous ion reducing antioxidant capacity (FRAP) assay and values of 0.078 ± 0.009 and 0.172 ± 0.027, respectively, in the copper ion reducing antioxidant capacity (CUPRAC) assay. When the DNA cleavage activities of NO and the NOAuNPs were evaluated via hydrolysis, both samples cleaved DNA starting at a concentration of 25 g/mL in the cell culture analysis, while the nanoformulation of the NO components gave greater therapeutic and anticancer effects. We determined that the Au nanoparticles were not toxic to A549 cells. Moreover, after treatment with the half-maximal inhibitory concentration (IC50), determined by the MTT assay with A549 cells, we found that at 24 and 48 h, while the necrosis rates were high in cells treated with NO, the rates of apoptosis were greater in cells treated with NOAuNPs. Notably, for anticancer treatment, activating apoptotic pathways that do not cause inflammation is preferred. We believe that these results will pave the way for the use of NOAuNPs in in vitro studies of other types of cancer. Conclusion In this study, AuNPs were successfully synthesized from N. officinale extract. The biosynthesized AuNPs exhibited toxicity to and apoptotic effects on A549 lung cancer cells. Based on these findings, we suggest that green-synthesized AuNPs are promising new therapeutic agents for lung cancer treatment. However, since this was an in vitro study, further research should be performed in in vivo lung cancer models to support our findings and to explain the mechanism of action at the molecular level.